GLOBAL CLIMATE CHANGE AND ITS CONSEQUENCES (British Journal of Global Ecology and Sustainable Development, 2025)
The article examines the pressing issues of global climate change, one of the most critical challenges facing the global community today. It substantiates that climate change is not only a representation of large-scale natural hazards but also a catalyst for various transformations in national economic sectors. The study analyzes the process, forecast, and consequences of climate change, highlighting the risks of disasters in both technological and social spheres as a result of global warming.